CH50 as a putative biomarker of eculizumab treatment in neuromyelitis optica spectrum disorder. Issue 1 (January 2021) - Namatame, Chihiro; Misu, Tatsuro; Takai, Yoshiki; Nishiyama, Shuhei; Nakashima, Ichiro; Fujihara, Kazuo; Aoki, Masashi
Abstract: Here we report 3 cases of neuromyelitis optica spectrum disorder (NMOSD), who were all treated with eculizumab and could be observed with monitoring serum C3, C4 and 50% hemolytic complement (CH50) before and after the treatment. Serum C3 and C4 were not dramatically changed during the treatment, in contrast serum CH50 level of each patient had diminished and kept under the detection limit after the treatment without clinical worsening, even in the situation of extending dosing. Serum CH50 level is useful to monitor the drug efficacy during eculizumab treatment. Abstract : Neuromyelitis Optica; Neuromyelitis optica spectrum disorder; Eculizumab; Biomarker; CH50; 50% hemolytic complement; C3; C4; C5; Astrocytopathy